Implantación de la contabilidad comercial por el sistema de cuenta multiple en la empresa spring cleaning de la ciudad de Cuenca, en el período enero a febrero del 2013 - Villavicencio Zambrano, María de Lourdes (2016)
The development of this research started with the purpose to create a Commercial Accounting through the Multiple Account System, in “Spring Cleaning” enterprise in Cuenca- Azuay Province, from January to February ,due the Financial Accounting problem, in order to the owner knows the real importance to carry out a control with thesupportof the Legal Regulation. Accounting plans, accounting books to register, to process the information and get the FinancialStatus, so the owner could make the correct decisions, it’s advisable to continue with the registration for getting the control of the enterprise. The results show us that this activity is profitable, because during the process we could realize that there were profits, and it is very important to create a better accountingprocess to permit to be safe about the real situation of the enterprise.